PERHITUNGAN PROFIT ASURANSI UNIT LINK DENGAN SURRENDER VALUE MENGGUNAKAN METODE PROFIT TESTING - PANJAITAN, HANNY; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika; Vol 9 No 1 (2020)DO - 10.24843/MTK.2020.v09.i01.p271, 2020)
Life insurance with surrender value is a type of insurance that allows the insured to cancel the contract. Unit-link life insurance is a combination of life insurance and investment. Profit testing method is used to find out the potensial loss or gain of unit link life insurance product. The aim of this research was to determine the potential benefits or losses of unit-linked life insurance product using a deterministic model. Results  of this research are the profit obtained by the insurance company for an insurance participant aged 35 years with a sum   and  in annual premiums are